Proceedings of the 3rd International Conference on Genetics of Aging and Longevity - Elena G. Pasyukova (Frontiers Research Topics, 2016)
In this book, we present a collection of articles covering a wide range of current aging research and highlighting its prospects and future directions. These articles are based on or related to the topics of the 3rd International Conference «Genetics of aging and longevity». The Conference took place 6-10 April, 2014 in Sochi, the city located on the Black Sea coast near the Caucasian mountains, in Russia. Top gerontologists and geneticists from 31 countries around the world came together to discuss current problems in many areas related to the genetics of longevity and mechanisms of aging. We would like to thank those of them who contributed to this e-Book by sharing latest achievements, ideas and hypotheses. We hope that this e-Book will come to notice of scientists interested in the development of genetics of aging and longevity and in the search for life-beneficial environments and life-prolonging interventions.